Re-emergence of human monkeypox 2022: its ecology and public health significance-short review article - Sanusi Karama, Rahama; Akinola, Ajoke; Kama, John (International Journal Of Community Medicine And Public Health, 2023)
Monkeypox virus (MPXV) is one of Orthopoxvirus subfamily, it’s refers to a zoonotic disease caused by MPXV. Human monkeypox, on the other hand, has a much lower morbidity and fatality rate than smallpox. Reference to the current resurgence, monkeypox outbreaks have been reported over the past 5 decades, 10 countries in Africa was initially discovered to be affected by the outbreak and subsequently 4 countries apart from Africa. Additionally, re-emergence of monkeypox in African countries, especially Nigeria about forty 40 years of the initial outbreak, midst 2010-2019. Climate change, deforestation, lack of proper health and research advance infrastructure among the society and uncontrol intake of bush meat in the African countries could have been the reason for the recent re-emergence of monkeypox within the communities. Public health significance of monkeypox outbreak could be the factors related to the vulnerability of the population towards MPXV when smallpox vaccination was stopped. Due to the rapid global outreach of monkeypox endemic, it should be therefore considered as a very serious re-surging pathogen in the world. However, detail and proper observational research could bring more light on the influence of MPXV on overall human population, together with the advancement in qualitative and quantitative of outbreak data collection, research in the current situation is crucial and need an emergency treat in order to encourage the researchers to improve more findings on the monkeypox outbreak, which will subsequently enhances appropriate case management and public health response.